THE RELATIONSHIP BETWEEN BREAST CARE IMPLEMENTATION AND POST PARTUM MOTHER'S MILK PRODUCTION AT PMB VERONIKA SINAGA BATAM CITY - Nurul Fajar Rina; Indah Mastikana; Sherly Mutiara (Bajang Institute, 2021)
Breast care is one of the most important efforts for post partum mothers with the aim of facilitating the production of breast milk.In order to reduce child morbidity and mortality, the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) in 2005 recommended that infants be breastfed for at least six months.The success rate of breastfeeding in Indonesia in 2013 was 54.3%,(Kemenkes RI, 2014). The success rate of breastfeeding in the Riau Islands in 2013 was 52.6%,(Kemenkes RI, 2014).Exclusive Breast Milk Coverage in Batam City 47% in 2017. The low coverage of exclusive breastfeeding may be due to the low awareness of the importance of breast care to support the production of breast milk,(Dinas Kesehatan Kota Batam, 2018).The purpose of this study was to explain the relationship between the implementation of breast care and the expenditure of breast milk in post partum mothers.The method used by the author is a descriptive type, in the form of research with a case study method or approach, with visits during the postpartum period to respondents aged 25 years P2A1 at PMB Veronika Sinaga Batam City and carried out 3 times.From the results of the study, it was shown that the breast care provided to the respondents went smoothly and there was an increase in the expenditure of breast milk after breast care was carried out.The conclusion in this study based on the results of the assessment and examination it was found that breast care for postpartum mothers was very influential, respondents were able to carry out breast care independently well, and the authors were able to apply midwifery care through a midwifery management approach and documented by the SOAP method.